An Analysis of the Relationship between Prices, Shopping Habits, Promotions, and Fashion Involvements in Impulsive Buying Decisions - Tibrani Tibrani; Shafie Mohamed Zabri; Lukmanul Hakim (Bina Nusantara University, 2024)
The research aimed to evaluate the direct and mediating association between impulsive buying behavior and the impact of several elements, such as costs, shopping lifestyle, promotion, and fashion engagement. Quantitative research was conducted by questionnaires to 100 participants, encompassing individuals from diverse age groups, jobs, and genders. However, only 88 questions were deemed legitimate and met the criteria for evaluation. In the interim, a total of 12 surveys were deemed unsuccessful due to their failure to fulfill the established criteria or the presence of incomplete responses provided by the participants. Researchers tested the relevance of the effect of each variable indicator that affected impulsive purchase using SmartPLS software. The findings indicate that among the factors examined, only one variable has a positive direction and a significant impact on impulsive buying through the intervening channel, as seen by a p-value of 0.010. Conversely, the remaining variables exhibit a lack of meaningful influence and display a negative direction. The result stipulates that the price is the primary criterion for individuals who make impulsive purchases to satisfy their fashion wants. These findings have the potential to address the idea that impulsive buying behavior is only determined by the intricate interplay of factors such as price, promotion, shopping lifestyle, and fashion engagement. Hence, it is necessary to employ alternative methodologies to benchmark various indicator variables to discover fresh findings on impulsive purchase attitudes on digital platforms in the modern day.